Policies to expand digital skills for the machine age - Martin, John P. (Bonn, 2017)
"A new technological epoch is underway – the so-called Machine Age – reflecting advances in artificial intelligence, digitalisation and Big Data. Some commentators have claimed that this epoch is different from previous ones in that it will produce large-scale technological unemployment, while others argue the contrary. Only time will judge who is right on this crucial debate. But the Machine Age will lead to major shifts in the demand and supplies of skills, especially digital skills. In this paper, I review the available cross-country evidence on the distribution of such digital skills across the adult populations within and across a large sample of OECD countries. I also review the evidence on participation rates in adult learning. Finally, I outline how education, training and labour market policies could help expand the supply of digital skills."